2020
DOI: 10.1016/j.jds.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 epidemic on the utilization of emergency dental services

Abstract: Background/Purpose: To assess how the current COVID-19 epidemic influenced peoples' utilization of emergency dental services in Beijing, China. Methods: The first-visit patients seeking emergency dental services before or at the beginning of the COVID-19 epidemic were retrieved. Their demographic characteristics and the reasons for visiting were recorded and analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
417
5
60

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 465 publications
(551 citation statements)
references
References 7 publications
(7 reference statements)
36
417
5
60
Order By: Relevance
“…In the current scenario, all elective or non-essential dental treatment for all patients should be deferred until the situation is regressing or under control [14]. There is a study conducted at a dental emergency department in Beijing, China [25], where they have observed an impact of the COVID-19 pandemic on the reporting of dental treatments, which has declined in the emergency department as compared to reporting pre-COVID-19. Due to the COVID-19 pandemic, less dental trauma has been reported and the proportion of dental and oral infection has increased while those of dental trauma and non-urgency have decreased [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the current scenario, all elective or non-essential dental treatment for all patients should be deferred until the situation is regressing or under control [14]. There is a study conducted at a dental emergency department in Beijing, China [25], where they have observed an impact of the COVID-19 pandemic on the reporting of dental treatments, which has declined in the emergency department as compared to reporting pre-COVID-19. Due to the COVID-19 pandemic, less dental trauma has been reported and the proportion of dental and oral infection has increased while those of dental trauma and non-urgency have decreased [25].…”
Section: Discussionmentioning
confidence: 99%
“…There have been online questionnaires supplied by some public tertiary dental hospitals to identify whether their dental patients were anxious or worried about the delayed dental visit. Although the public dental hospitals still offered emergency treatments for patients, significant utilization reduction in emergency dental services was observed at the beginning of the COVID-19 epidemic [5]. Some dental specialists were also concerned about exploding visits after the end of the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…* Xiaoqiang Liu liuxiaoqiang@bjmu.edu.cn showed that patients were less willing to go to dental institutions, and the proportion of dental and oral infection in emergency dental care rose at the beginning of the epidemic [5]. The public tertiary dental hospitals in China always play a key role in dental health services.…”
Section: Introductionmentioning
confidence: 99%
“…(2) patients with urgent or post-op complications that should come back to the clinic [10][11][12][13]; (3) patients or relatives with motor difficulties of any nature that prevented the correct capture of images.…”
Section: Study Samplementioning
confidence: 99%